Fluorescence studies of Pr3 +, Sm3+, and Ho3 +, amino acid ternary complexes in aqueous solution - Sharma, Y.; Bishnoi, N.; Surana, S.; Bhutra, M.; Tandon, S.; Tandon, K. (Rev. Téc. Fac. Ing. Univ. Zulia)
Véase archivo PDF